Transgelin mediates transforming growth factor‐β1‐induced proliferation of human periodontal ligament cells. (7th June 2017) - Mitarai, H.; Wada, N.; Hasegawa, D.; Yoshida, S.; Sonoda, M.; Tomokiyo, A.; Hamano, S.; Serita, S.; Mizumachi, H.; Maeda, H.
Abstract : Background and Objective: Human periodontal ligament cells (HPDLCs) express transforming growth factor‐β1 (TGF‐β1) that regulates differentiation and proliferation, and plays key roles in homeostasis of PDL tissue. Transgelin is a cytoskeleton‐associated protein with an Smad‐binding element in its gene promoter region. In this study, we examined the localization and potential function of transgelin in PDL tissue and cells. Material and Methods: Microarray analysis of HPDLC lines (2‐14, 2‐23 and 2‐52) was performed. Expression of transgelin in HPDLCs was examined by quantitative reverse transcription–polymerase chain reaction, immunofluorescence staining and western blot analysis. Effects of TGF‐β1 and its signaling inhibitor, SB431542, on transgelin expression in HPDLCs were examined by western blot analysis. The effects of transgelin knockdown by small interfering RNA (siRNA) on HPDLC proliferation stimulated by TGF‐β1 were assessed by WST‐1 assay. Results: In microarray and quantitative reverse transcription–polymerase chain reaction analyses, the expression levels of transgelin ( TAGLN ) in 2‐14 and 2‐23 cells, which highly expressed PDL markers such as periostin ( POSTN ), tissue non‐specific alkaline phosphatase ( ALPL ), α‐smooth muscle actin ( ACTA2 ) and type I collagen A1 ( COL1A1 ), was significantly higher than those in 2‐52 cells that expressed PDL markers weakly. Immunohistochemical and immunofluorescence staining revealed expression of transgelin in rat PDL tissue and HPDLCs. In HPDLCs, TGF‐β1 treatment upregulated transgelin expression, whereas inhibition of the type 1 TGF‐β1 receptor by SB431542 suppressed this upregulation. Furthermore, TAGLN siRNA transfection did not promote the proliferation of HPDLCs treated with TGF‐β1. The expression levels of CCNA2 and CCNE1, which regulate DNA synthesis and mitosis through the cell cycle, were also not upregulated in HPDLCs transfected with TAGLN siRNA. Conclusion: Transgelin is expressed in PDL tissue and might have a role in HPDLC proliferation induced by TGF‐β1 stimulation.